The changing profile of neonatal pathogens and susceptibility pattern: prospective observational study from a tertiary center in South India - Krishnan Chakkiyar; Gireeshan Veluthedath Kuzhiyil; Maya Sudhakaran; Shameem Anathan Mohammed; Nabeel Valappil Faisal; Mohandas Nair (Journal of Research in Clinical Medicine)
Introduction: Changing the pattern of neonatal pathogens poses challenges to the management of neonatal sepsis. Profile and antimicrobial susceptibility of neonatal pathogens were evaluated in this prospective observational study in a tertiary center. Methods: Neonates with risk factors and clinical features of sepsis were screened. Blood culture performed in positive-screen babies. Antimicrobial susceptibility was also evaluated. Statistical significance was tested by the chi-square test and t test accordingly. Univariate analysis was performed to study possible correlations in this regard. Results: Out of 431 suspected cases, 89 neonates (20.65%) had sepsis. The rate of early and late-onset sepsis (LOS) was 48.3% and 51.7%, respectively. The clinical spectrum included septicemia 68 (76.5%), congenital pneumonia 13 (14.7%), meningitis 5 (5.7%), and septic arthritis 3 (3.4%), respectively. Gram-positive bacteria constituted 61 (68.5%), while gram-negative was 28 (31.5%) (P<0.05). Staphylococcus aureus (23.6%) and methicillin-resistant S. aureus (MRSA) (22.5%) were the most common isolates. Acinetobacter (15.8%), coagulase-negative staphylococcus areus (CoNS) (11%), Klebsiella (7.9%), enterococci (8%), E. coli (4.5%), and ß hemolytic streptococci (1 case) were other detected pathogens. MRSA, Acinetobacter, and coagulase-negative S. aureus as a single entity involved in sepsis pathogenesis (50.6%) showed a positive correlation with inborn babies, pre-term, low birth weight, and early-onset sepsis (OR; 95% CI: 2.20; 0.94–5.20, 1.82; 0.79–4.22, 1.25; 0.55–2.89 and 1.05; 0.46–2.50 respectively). Susceptibility pattern was penicillin (12.3%), ampicillin (6.7%), cloxacillin (42.9%), cefotaxime (8%), cefazolin (37.9%), cefoperazone sulbactam (81.5%), piperacillin-tazobactam (68.9%), gentamicin (63.5%), amikacin (47.9%), vancomycin (88.9%), linezolid (88.6%), co-trimoxazole (55.4%), and clindamycin (50%). Conclusion: Gram-positive pathogens and opportunistic pathogens like Acinetobacter predominate over the conventional gram-negative pathogens in neonates. Of note, penicillin, ampicillin, and cefotaxime are not suitable for the empiric treatment of neonatal sepsis.